Comparative Evaluation Methods of Comprehensive Soil Fertility in Jiangsu’s Coastal Saline–Alkali Land - Zhiwang Wang; Shihang Wang; Lingying Xu; Qiankun Guo; Yuqi Chen; Weiwen Qiu; Jiabei Sun (Land)
In coastal saline–alkali regions, the intrusion of saline water exacerbates the nutrient depletion in the plow layer, posing a significant challenge to agricultural productivity. Given the limited understanding of soil fertility in these areas and the inconsistent results among different assessment methods, this study aims to develop a more accurate and reliable soil fertility evaluation system. To achieve this objective, 108 topsoil samples were systematically collected from saline–alkali lands in Jiangsu Province. Several key soil fertility indicators, including soil pH, total salinity (TS), soil organic matter (SOM), total nitrogen (TN), total phosphorus (TP), total potassium (TK), alkaline-hydrolyzable nitrogen (AN), available phosphorus (AP), and available potassium (AK), were comprehensively evaluated. Four advanced methods, namely principal component analysis indexing–linear scoring (SQIPCAL), principal component analysis indexing–nonlinear scoring (SQIPCANL), modified Nemerow–linear scoring (SQINemeroL), and modified Nemerow indexing–nonlinear scoring (SQINemeroNL), were employed to conduct a multi-dimensional examination of soil fertility. Additionally, principal component analysis (PCA) was utilized to establish a minimum data set (MDS), which was then compared with the total data set (TDS) for a more precise assessment of soil fertility. Linear scoring methods (SQIPCAL and SQINemeroL) had higher semi-variogram R2 values compared to nonlinear methods. Moreover, under the SQIPCAL and SQINemeroL evaluation methods, a strong correlation was observed between the TDS and MDS, with R2 values reaching 0.63 and 0.65, respectively. Based on these findings, the SQINemeroL method, integrated with MDS, is recommended as an effective approach for soil fertility assessments in coastal saline–alkali regions in Jiangsu Province. This research not only enriches the theoretical understanding of soil fertility in such regions but also provides practical insights for sustainable agricultural management.